2003
DOI: 10.1016/s0041-624x(03)00097-0
|View full text |Cite
|
Sign up to set email alerts
|

Guided wave dispersion curves for a bar with an arbitrary cross-section, a rod and rail example

Abstract: Theoretical and experimental issues of acquiring dispersion curves for bars of arbitrary cross-section are discussed. Since a guided wave can propagate over long distances in a structure, guided waves have great potential for being applied to the rapid non-destructive evaluation of large structures such as rails in the railroad industry. Such fundamental data as phase velocity, group velocity, and wave structure for each guided wave mode is presented for structures with complicated cross-sectional geometries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
300
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(333 citation statements)
references
References 23 publications
1
300
0
1
Order By: Relevance
“…The SAFE method has seen extensive use in the elastic waveguide literature in recent years (see for example [7][8][9][10]). The use of this method to study energy dissipation is, however, less well reported and it is only recently that sound attenuation has been included in the SAFE method for elastic waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…The SAFE method has seen extensive use in the elastic waveguide literature in recent years (see for example [7][8][9][10]). The use of this method to study energy dissipation is, however, less well reported and it is only recently that sound attenuation has been included in the SAFE method for elastic waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…This allows the system potentially capable to be permanently installed on the structure enabling it to be monitored continuously. Guided Wave technology has been widely applied in metallic structures in order to inspect pipes, plates, rails (Alleyne and Cawley 1992a;Alleyne and Cawley 1992b;Cawley et al 2003;Hayashi et al 2003;Rose et al 2004). During the 1990s, significant research was focused on pipe inspection (Ditri and Rose 1992;Alleyne et al 1998;Lowe et al 1998), because there was a need to assess in a rapid manner the integrity of hundreds of kilometres of pipelines in the oil & gas, nuclear and chemical industries.…”
Section: Guided Wave Technology In Compositesmentioning
confidence: 99%
“…Different techniques have been proposed, such as traditional Finite Element Method (FEM) (Lissenden et al 2009;Song et al 2009;Ricci et al 2014), semianalytical finite element method (SAFE) (Hayashi et al 2003;Deng and Yang 2011;Rose 2014), finite differences (Saenger and Bohlen 2004;Moczo et al 2007) or applying the elasticity theory using the global matrix and transfer matrix (Wang and Yuan 2007;Karmazin et al 2011Karmazin et al , 2013. Finite Element Methods have limitations due to the available computational resources, since for high frequencies a very fine discretization, both temporal and spatial, is necessary to comply with the Nyquist theorem and to ensure a minimum number of elements per wavelength in order to replicate the wave.…”
Section: Simulationmentioning
confidence: 99%
“…[23][24][25][26], and so this is only briefly reported here. The displacements 1 â€Č in region Ω 1 of the pipe (regions Ω 1 and Ω 3 are assumed to be identical) are expanded over the pipe eigenmodes to give…”
Section: Eigenvalue Analysismentioning
confidence: 99%